Konstruksi Urban Marital Satisfaction Scale (UMSS): Alat Ukur Kepuasan Pernikahan dengan Konteks Perkotaan Indonesia - Bahtiar, Fadhilatussyifa Auliyarahmani; Oktarina, Nina; Khoir, Ahmad Kholiqul; Nugroho, Bambang; Jarar, Syeda Parsa; Seniati, Ali Nina Liche (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The Urban Marital Satisfaction Scale (UMSS) was developed to measure marital satisfaction among couples living in urban areas by emphasizing financial and communication aspects that are often overlooked in previous instruments. This scale was constructed based on the theoretical framework of Spanier and Busby, which includes three key dimensions: dyadic consensus, dyadic cohesion, and dyadic satisfaction. A total of 52 initial items were developed and tested through readability trials, expert judgment, and item analysis. Based on empirical testing with married individuals aged 20 to 40 years, who had been married for at least two years, a total of 21 items were retained in the final version of the scale. The item selection process involved eliminating poorly performing items and revising ambiguous or culturally unfamiliar statements. Psychometric evaluations showed that the UMSS demonstrates strong internal consistency and good construct validity. The scale is also able to distinguish between individuals with high and low levels of marital satisfaction. These findings indicate that the UMSS is a reliable and valid measurement tool that can be used in psychological assessments and interventions targeting urban couples.